Effects of storage on quality traits of sausages made with chicken breast meat affected by wooden breast - de Oliveira, Rodrigo Fortunato [UNESP]; Fávero, Maísa Santos [UNESP]; de Mello, Juliana Lolli Malagoli [UNESP]; Ferrari, Fábio Borba [UNESP]; Cavalcanti, Erika Nayara Freire [UNESP]; de Souza, Rodrigo Alves; Pereira, Mateus Roberto [UNESP]; Giampietro-Ganeco, Aline; Villegas-Cayllahua, Erick Alonso [UNESP]; Fidelis, Heloisa de Almeida [UNESP]; de Souza, Pedro Alves [UNESP]; Borba, Hirasilva [UNESP] (MDPI, 2021)
The aim of this study was to examine the effects of storage on the quality of sausages made with breast from chickens affected by wooden breast myopathy (WBM). Breast samples from male broilers slaughtered at 48 days old were used. Normal (absence of myopathy), moderate degree (hardness only in one region of the breast) and severe degree samples (hardness over the entire length of the breast) were processed into sausages and evaluated prior to storage and after being vacuum-packed and stored for 7, 14, 21 and 28 days at 4 °C. There was a decrease (p < 0.001) in pH and an increase (p < 0.001) in cooking weight loss in samples of sausages, regardless of the myopathy, after 28 days of storage. Sausages produced with chicken breast samples affected by wooden breast myopathy presented higher (p < 0.0001) moisture concentration (72% for the severe degree) and higher (p = 0.0224) protein concentration (17.27% and 17.36%, respectively, for the moderate and severe degrees) than sausages made of normal samples (70.72% and 14.32%, respectively). The results indicate that sausages produced with meat from birds moderately and severely affected by the myopathy show higher oxidative stability. Fresh sausages produced with breast meat from birds affected by wooden breast syndrome may be stored (4 °C) for up to 28 days without exhibiting the characteristic rancid taste and smell. In sensory analysis, no differences were observed between the formulations, which suggests that the consumers approved the samples regardless of the disease severity in the meat used for the making of the sausages. The current results show that chicken meat affected by wooden breast myopathy can be used for producing fresh sausages in the industry.
Keywords: Chicken breast meat; Cooling storage; Meat quality; Muscle disease; Wooden breast